Magnetic properties of artificially designed magnetic stray field landscapes in laterally confined exchange-bias layers. (27th June 2018) - Mitin, D; Kovacs, A; Schrefl, T; Ehresmann, A; Holzinger, D; Albrecht, M
Abstract: Magnetic stray fields generated by domain walls (DWs) have attracted significant attention as they might be employed for precise positioning and active control of micro- and nano-sized magnetic objects in fluids or in the field of magnonics. The presented work intends to investigate the near-field response of magnetic stray field landscapes above generic types of charged DWs as occurring in thin films with in-plane anisotropy and preferential formation of Néel type DWs when disturbed by external magnetic fields. For this purpose, artificial magnetic stripe domain patterns with three defined domain configurations, i.e. head-to-head (tail-to-tail), head-to-side, and side-by-side, were fabricated via ion bombardment induced magnetic patterning of an exchange-biased IrMn/CoFe bilayer. The magnetic stray field landscapes as well as the local magnetization reversal of the various domain configurations were analyzed in an external magnetic field by scanning magnetoresistive microscopy and compared to micromagnetic simulations.